The effect of deposition time on the structural properties of ZnO nanorods prepared by sol-gel immersion method / Noor Aini Amir - Amir, Noor Aini (2009)
ZnO nano rods were successfully grown on Au coated Si substrate and Si bare substrate. The growth was using sol-gel immersion method at different deposition time which is 2, 4, 6, 8, 10 and 12 hours. In the presence of Au, growth rate of nanorods is much faster as it performs as a catalyst by decreasing the growth time of ZnO nanorods to half compared to growth on Si substrate without Au coated. Using Scanning Electron Microscope (SEM), changes in growth of nanorods at different deposition time was captured and the structural properties were discussed. Besides that, the optical property was also studied using photoluminescence spectrometer (PL) and had been discussed.